Anticancery Activity In Vitro Polysaccharides Fermented from Brown Algae. (October 2019) - Su, Yue; Wang, Zhongjian; Li, Kunlun; Zhao, Lin
Abstract: Cancer has become one of the world's leading causes of death, and the current treatment of cancer still cannot evade the side effects of chemotherapy drugs. In this study anticancer effect of fucoidan isolated from brown seaweeds polysaccharide was investigated. The obtained seaweeds polysaccharide is mainly prepared by fermenting, separating and purifying seaweeds by a mixed strain of yeast and Lactobacillus plantarum. Polysaccharides in algae can inhibit or kill tumor cells by enhancing the body's immune function and defense capability. Intake of polysaccharides can activate or activate macrophages, thus inducing them to produce tumor necrosis factor. Polysaccharides extracted from seaweed were formulated into different concentrations of drugs to treat 231 cells and HCT-116 cells to detect the effects of extracts on the two cancer cells. When no drug is added to the cell suspension, the cell grows well. The polysaccharides had no cytotoxicity on HCT-116 cells under 500 μg/mL and inhibited cell viability at concentration of 2000 μg/mL. As for 231 cells, the cell survival rate was 61.08% at 1000 μg/mL. The present research clearly indicated the cytotoxicity of seaweeds polysaccharide in HCT-116 cells and 231 cells through adding them. These results also suggested the seaweeds polysaccharide may be a powerful agent against cancer cells.